Essays on corporate social irresponsibility - Rezende, Lígia de Azevedo (2023)
This dissertation explores, along four independent chapters, the phenomenon of Corporate Social Irresponsibility (CSI). Chapter 1 presents a major literature review on the topic in order to synthesize this body of knowledge and propose a research agenda for future studies. The second chapter investigates the impacts of CSI on the employees of irresponsible firms, examining how such events affect their careers and financial outcomes. The third chapter examines how firms’ decision to engage in greenwashing – a common and deceitful disclosure strategy – is influenced by stakeholders’ difficulty in observing and assigning blame for CSI to specific firms. Finally, chapter 4 explores how shareholders respond to CSI through ESG-related activism, and how the language in sustainability reports may influence their responses. Taken together, the four chapters of this dissertation bring implications to several streams of research, especially to the literatures on corporate social (ir)responsibility, non-market strategies, stakeholder theory, impression management and information disclosure.